Levels of ractopamine in the diet and effects on performance and carcass characteristics of finishing pigs - Bellaver, Claudio; Fialho, Elias Tadeu; Fávero, Jerônimo Antônio; Ajala, Luis Carlos; Neto, José Severino (Pesquisa Agropecuaria Brasileira, 1991)
The experiment was arranged in completely randomized block desing using pigs fed diets with 0, 10 and 20 ppm of RAC and 16% crude protein (CP) (treatments (T) 1, 2 and 3, respectively), and 20 ppm of RAC with 13% CP (T4). Diets were based on corn/soybean meal. There was no significant (P > 0.05) difference in consumption among treatments. T2 presented higher average daily gain than T4 and better feed gain ratio (FG) than T1 (P < 0,05). The decrease in CP (T3 vs T4) gave worst FG (P < 0.05). It was found that carcasses on T2 (16% CP, 10 ppm RAC), were significantly (P < 0.05) lower than T1 in ham fat weight, fat thickness measured at 10th rib and P2. There was no additional effects due to increase in RAC (T2 vs T3). It was concluded that there was an improvement in performance and carcass characteristics of swine fed 10 ppm of RAC and 16% CP.